(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: One of the rare disabilities include patellar instability. It happens mostly in younger patients. According to biochemical studies, medial patella-femoral ligament (MPFL) prevents lateral displacement of patella. MPFL mainly acts as the main soft tissue stabilizer. Anatomical reconstruction of MPFL is a surgical procedure which is used for patients having severe recurrent patellar dislocation to restore stability to the knee. In order to treat patellar instability, there are several surgical procedures described which include both soft tissue procedures like MPFL reconstruction and bony procedures. Objective: To determine the functional outcome of medial patella-femoral reconstruction by using the semitendinosus tendon auto-graft on patients having recurrent patella dislocation Study design: A descriptive study. Duration and place of study: This study was conducted at Hamdard University Hospital Karachi Pakistan from December 2024 to December 2025 Methodology: This research was conducted in our hospital. Patients were aged from 18 years to 45 years and both the genders were included. All the patients were having unilateral recurrent patella dislocation. Patients with MPFL tear, with or without meniscal injury detected clinically and confirmed by MRI were included. Clinical examination along with the complete history of all the participants was taken.The International Knee Documentation Committee (IKDC) score was used to assess pre-operative functional status. All the demographic data, mode injury, and type of injury was recorded. SPSS version 23 was used to analyse the data. Parametric t-test was used to compare pre-operative and post-operative IKDC scores. Results: There were a total of 60 patients enrolled in this study. There were 22 males and 38 females included in this study. The mean age calculated was 24.1 ± 11.4 years. 60% of the patients were presented with isolated MPFL injury. Right sided recurrent patella dislocation was noted in 61.6% patients. The majority of the patients had sports related injuries, representing 53.3% of the total participants. The majority of the patients gave pre-operative history of guarded walking (68.3%). 8.3% were giving signs of instability or giving away, 36.6% were giving signs of locking, and 35% were giving signs of activity-related pain. Clinical examination showed a positive patella apprehension sign in 81.6% of the patients. At 1 year of follow-up, the mean IKDC score improved from 42.4 ± 9.3 (pre-operative) to 86.3 ± 12.6 (post-operative). Conclusion: Medial patello-femoral ligament (MPFL) reconstruction using semitendinosus tendon auto-graft is an effective surgical method to treat recurrent patella dislocation.